Study on Cell Anatomy of Rafflesia kerrii Meijer in Lojing Highlands, Kelantan - Asfarina Ismail (2015)
Rafflesia kerrii Meijer from the family Rafflesiaceae is one of the fifth species being described earlier in Peninsular Malaysia. Rafflesia species is one of the endangered species in Lojing Highlands. Recently, irresponsible human activities especially extensive agriculture in Cameron Highlands have been extended to Lojing Highlands. It is very threatening to the endangered species in Lojing Highlands. Sample of R. kerrii Meijer was collected from a locality in Lojing Highlands, which is Pos Hendrop. The purpose of this S study is to examine the anatomical characteristics of R. kerrii Meijer in Lojing Highlands and to compare the anatomical structures of R. kerrii Meijer found in Lojing Highlands to the same species found in Thailand. There are four parts being studied, which are perigone lobe, window, ramenta and processes. The methods used for the anatomical study were micro techniques analysis by using sliding microtome. The anatomy of R. kerrii Meijer in Lojing Highlands showed that all the four parts being observed had simple and uncomplicated structure. Epidermal cell layers present at both the upper and lower layers of the plant. The presence of ground tissues were mainly composed of parenchyma cells. Undeveloped vascular bundle also present in the ground tissues. Based on the overall results, the comparison on anatomical characteristics between R. kerrii Meijer found in Lojing Highlands to the same species found in Thiland have the same types of major tissues. However, there are a few differences in the presence of starch grains, distance between vascular bundles in perigone lobe parts, and the presence of trichome at window part.